The Influence of Organizational Culture and Competence on Employee Performance Mediated by Organizational Commitments in the Procurement of Goods and Services Secretariat Regency of Karangasem - Aryani, Ni Ketut Yuni; Sapta, I Ketut Setia; Sujana, I Wayan (Asia Pacific Journal of Management and Education (APJME), 2021)
Employees have a very important role, where they must spare their energy and thoughts to achieve company goals. The management of corporate culture is directed to the ability to encourage company performance through improving employee performance. The purposes of this study are to examine and analyze the effect of organizational culture and competence on organizational commitment, employee performance, and employee performance. The population and the respondents were 76 people in the Karangasem Regency Government. This study used the SEM analysis with SmartPLS 3.0 program. The findings indicate that organizational culture has a positive effect on organizational commitment and employee performance. Competence affects both the organization's commitment and employee performance positively. Organizational commitment also affects the performance of employees positively and and mediate the relationship between organizational culture and competence on employee performance.